The Influence of Managerial Roles and Empowerment on Innovations with Competitive Implications - Sri Rochani Mulyani; Taufik Zulfikar; Sumeidi Kadasrisman; Erika Nurmartiani (Budapest International Research and Critics University, 2021)
Breakthrough innovations in service organizations can be realized through the development of new business models, new services, new customer interfaces, and administrative innovations involving managerial roles and empowerment, all of which will influence competitiveness. This study aimed to determine and analyze the influence of managerial roles on open innovation and its implications for competitiveness. Purposive sampling of around 200 people was used to determine the population, which consisted of structural officials at universities in West Java. Path analysis was used as the analytical method. The findings of this study revealed that managerial roles and empowerment had a favorable and significant impact on innovation, either partially or simultaneously. Furthermore, innovation had a beneficial and considerable impact on competitiveness.